2010
DOI: 10.1099/vir.0.018663-0
|View full text |Cite
|
Sign up to set email alerts
|

Differences and changes in human papillomavirus type 16 variant status in human immunodeficiency virus-positive adults are not uncommon

Abstract: Human papillomavirus type 16 (HPV-16) genotype variants have been the subject of several investigations, but study participants have rarely been sampled more than once. In this study, among a cohort of human immunodeficiency virus (HIV)-infected adults, HPV-16 variants were investigated in samples collected concurrently from the anus and cervix, as well as in serial samples collected from the same anatomical site at 12-month intervals. HPV-16 variants in stored extracts of cervical and anal samples were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…African HPV16 variants were found more commonly among African-American vs. other participants. Few studies have examined HPV16 genotype variants in HIV-infected MSM but these have demonstrated that European variants are the most common [23], [42], [43]. Further study is needed to examine genotype variants in HIV-infected MSM, given their possible association with HPV persistence and the increased risk of cancer with non-European variants [7], [26], [29], [39], [45].…”
Section: Discussionmentioning
confidence: 99%
“…African HPV16 variants were found more commonly among African-American vs. other participants. Few studies have examined HPV16 genotype variants in HIV-infected MSM but these have demonstrated that European variants are the most common [23], [42], [43]. Further study is needed to examine genotype variants in HIV-infected MSM, given their possible association with HPV persistence and the increased risk of cancer with non-European variants [7], [26], [29], [39], [45].…”
Section: Discussionmentioning
confidence: 99%
“…Mayrand et al [13] demonstrated different DNA polymorphisms in 4 of 50 women by analysis of single-stranded conformation polymorphisms of HPV-16 variants in consecutive specimens. An even higher disconcordance rate was detected by pyrosequencing of HPV-16 variants in a recent study of human immunodeficiency virus-infected adults [14]. Other studies have reported identical variants in consecutive samples positive for HPV-16 [11,12] or other high-risk types [15].…”
Section: Prospective Studies Of the Persistence Of Human Papillomavirmentioning
confidence: 93%
“…Another study that analyzed the HPV16 variant status in paired-enrollment and follow-up cervical specimens showed that changes in the HPV16 variants occurred in four of 86 women (4.7z) (33). Among a cohort of human immunodeficiency virus (HIV)-infected adults, eight of 59 women (13.6z) showed discordant HPV16 variants in sequentially collected anal and cervical samples (34). These data suggest that natural infections can result from continuous exposure to infection with different HPV16 variants.…”
Section: Quasispeciesmentioning
confidence: 99%